Circumferential intimal tear with thrombosis of right superficial femoral artery due to penetrating injury by bull horn: A case report. (February 2022) - Bhatt, Swechha; Vaidya, Satish; Man Karmacharya, Robin; Tamang, Ashish; Manandhar, Anu; Neupane, Manish
Abstract: In agrarian countries where bulls are used for farming and stock breeding, bull horn injuries are common. Bull horn injuries range from blunt trauma to penetrating injuries, which can cause massive hemorrhage. Vascular injuries to the limbs by goring bull horn injury usually involve transection of vessels but rarely cause intimal tear with thrombus formation. Here, we report an unusual case of a 33-year-old male with circumferential intimal tear with thrombosis in the subintimal region of the right superficial femoral artery without transection of the vessel following penetrating injury to the right thigh caused by a bull's horn. There was a pulse deficit above the popliteal artery, and Doppler ultrasonography revealed decreased flow indicative of underlying femoral vessel injury for which the wound was surgically explored. It was followed by right superficial femoral arteriotomy at the site of the thrombus with the evacuation of a 6 cm long clot, revealing a 6 cm long endothelial injury in the same vessel. Next, an interposition reversed saphenous graft was placed in the same location. Following this, Doppler ultrasonography was done that revealed restoration of blood flow to the site of thrombosis. Thus, in a case of bull horn injury, thrombosis should be ruled out with prompt surgical wound exploration despite the presence of an intact vessel. Highlights: Bull horn injury to extremities can cause intimal tears with subintimal thrombosis, partially impeding blood flow. Diagnostic dilemma can occur due to contrasting radiological and clinical findings in injuries with vascular occlusion. Surgical wound exploration without CECT scan can be considered a diagnostic and therapeutic approach for revascularization.